Estimation Of Biochemical Status And Immunostimulant Potential Of Chosen Fruits - S. PAULSI; P. DHASARATHAN (International Journal of Pharma and Bio Sciences, 2011)
In the present study investigates biochemical status and immuno-stimulant potential of different fruits such as Paneer guava, Custard apple, Pomegranate, Muskmelon, Carambola and Sapota. The amount of carbohydrate was high in Custard apple followed by Paneer guava, Pomegranate, Carambola, Muskmelon and Sapota. The amount of protein was high in Paneer guava followed by Custard apple, Sapota, Pomegranate, Muskelon and Carambola. The Percentage of T cells were varied remarkable due to exposure of antigens (Staphylococcus aureus was 64, Streptococcus pyogenes was 67, Bacillus subtilis was 62, Salmonella typhi was 64 and Shigella sonnei was 67). Percentage of T cells in fruits extract administered mice showed in the following order Paneer guava (54), Sapota (56%), Muskmelon (57), Custard apple (58), Pomegranate (59) and Carambola (59). The Percentage of B cells composition was 38, 43, 37, 40 and 35 in animals administered with antigens of Staphylococcus aureus, Streptococcus pyogenes, Bacillus subtilis, Salmonella typhi and Shigella sonnei respectively. B cells in fruits extract administered animals showed 45, 44, 43, 40, 39 and 37 percentages in Muskmelon, Paneer guava, Custard apple, Carambola, Pomegranate and Sapota respectively. The results showed injection of antigen in paw, after 3hrs paw volume is increased about 8mm than the normal. The paw volume was increased about 10mm at 24hrs and after 24hrs the paw volume was increased more than 10mm in all the five antigens. The immunoglobin concentration of Ig G was observed in the antigen administered mice and fruit extracts administered mice. From the results the chosen fruits have effective immunostimulant potential.